Age-Adjusted Alignment Goals Have the Potential to Reduce PJK - Lafage, Renaud; Schwab, Frank; Glassman, Steve; Bess, Shay; Harris, Bradley; Sheer, Justin; Hart, Robert; Line, Breton; Henry, Jensen; Burton, Doug; Kim, HanJo; Klineberg, Eric; et al. (Spine (Philadelphia, Pa. 1976), 2017)
Retrospective cohort. To explore proximal junctional kyphosis (PJK) as a function of age-adjusted surgical correction goals. Recent adult spinal deformity (ASD) studies show that alignment targets are age-specific. Despite recognizing age and malalignment as PJK risk factors, no study has assessed the age-specific effects of alignment on PJK. ASD patients with fusions to the pelvis were included and stratified into three groups: young adults (YA <40 years old), middle aged (MA: 40-65 years old), and the elderly (ED >65 years old). Analysis of variance compared the groups with respect to 1-year postoperative alignments and 1-year offsets from age-specific alignment targets. A total of 679 patients were enrolled (mean age = 61 years old, 77% female, body mass index = 28.1). At 1 year postoperatively, there was a significant decrease in pelvic tilt (PT; 29-23°), spinopelvic mismatch (pelvic incidence [PI]-lumbar lordosis [LL]) (28-5°), and sagittal vertical axis (SVA; 110-37 mm); overall incidence of PJK was 45.1%. Stratification by age (YA, n = 28; MA, n = 389; ED, n = 262) revealed an increase in PJK incidence with age: YA = 17.9%, MA = 43.8%, and ED = 50.2% (P < 0.001). PJK patients had smaller postoperative PI-LL mismatches (ED 0.8° vs. 9.8°, MA 3.1° vs. 7.3°) than non-PJK patients, without any significant differences in PT or SVA. Analysis of the postoperative offsets from age-specific norms revealed that PJK patients in the two older subgroups and in the study cohort as a whole were overcorrected as compared to non-PJK patients (PI-LL offset-all: -5.2° vs. 2.8°, MA: -1° vs. +4°, ED: -11° vs. -2°; SVA offset-all: -10 mm vs. 7 mm, MA: -3 mm vs. 10 mm, ED: -18 mm vs. -6 mm). The correlation coefficients between PJK angles and the offsets from age-adjusted objective were small (0.320 for PI-LL, 0.114 for PT, and 0.136 for SVA). Overall, this study suggests that PJK patients were overcorrected when compared to age-adjusted alignment goals. Certainly, elderly patients are subject to independent risk factors for PJK, making the prevention of PJK complex. However, individualized optimization of surgical alignment can improve outcomes. This emphasizes the need for surgeons to incorporate age-specific alignment targets into the standard preoperative planning process. 3.